Дослідження «цитаделі» Херсонеса Таврійського у 2009 р. - Домановський, А.М.; Сорочан, С.Б. (Археологічні дослідження в Україні, 2010)
The article discusses the archaeological studies of the socalled «citadel» of the National Preserve of Tauric Chersonesos in 2009. Field research was directed to making topographic survey of the object, collecting the available material, the most interesting of which was a fragment of the Early Byzantine glass bracelet from the area of medieval thermae. The main task of work in the Archives of the Preserve was to adjust the existing drawings, plans, and schemes of buildings on the territory of «citadel» and further to make plans in accordance with the building periods.